Bleeding diathesis is associated with an A15T heterozygous mutation in exon 2 of the plasminogen activator inhibitor type 1 - JANKUN, JERZY (D.A. Spandidos, 2010)
In the present study, we present a 60-year-old woman of American Indian descent with a life-long history of bleeding diathesis. She had a history of recurrent and prolonged bleeding such as mild epistaxis, gingival bleeding and microscopic hematurias. She also experienced a severe bleeding event after surgery. The patient had a large family with a history of a tendency of bleeding, severe in some cases. Hemostatic screening studies revealed no abnormalities, which could explain the bleeding tendency. Clot formation of sodium-citrated blood was analyzed by thromboelastography, which suggested a low platelet count or plasminogen activator inhibitor-1 (PAI-1) deficiency. However, her platelet count was slightly elevated. Subsequent sequencing of the PAI-1 gene revealed a heterozygous Ala15Thr mutation in the signal peptide. This type of deficiency is related to dynamics of PAI-1 secretion rather than its low levels or activity. We concluded that the PAI-1 mutation was likely the etiology of the bleeding diathesis in this patient.